Workers' Rights as Human Rights: Organized Labor and Rights Discourse in Canada - Savage, Larry (Labor Studies Journal, 2009)
In the wake of a series of prolabor Supreme Court decisions in Canada, the mantra of “workers' rights as human rights” has gained unprecedented attention in the Canadian labor movement. This article briefly reviews the Canadian labor movement's recent history with the Supreme Court before arguing that elite-driven judicial strategies, advocated by several academics and Canadian unions, threaten, over time, to depoliticize traditional class-based approaches to advancing workers' rights. The argument is premised on the notion that liberal human rights discourse does little to address the inequalities in wealth and power that polarize Canadian society along class lines.
Keywords: BC Health Services decision; Canada; Supreme Court; Unions; labor rights as human rights; workers'rights as human rights